2002
DOI: 10.1002/app.10003
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and experimental studies of emulsion copolymerization systems. III. Acrylics

Abstract: ABSTRACT:Using a previously published model and continuing the series of papers started with styrenic copolymers, predictions for evolution of conversion and average particle diameter in batch experiments are compared against experimental data for four emulsion copolymerizations involving at least one acrylic monomer: (1) methyl methacrylate/butyl acrylate, (2) methyl methacrylate/butadiene, (3) methyl methacrylate-vinyl acetate, and (4) butyl acrylate/vinyl acetate. For each system a fraction of factorial exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 53 publications
(72 reference statements)
3
18
0
4
Order By: Relevance
“…Difficulties to quantitatively describe the changes of the particle diameter in VA/BA emulsion copolymerization reactions were also reported by Saldívar et al [5], despite having used eight adjustable parameters to fit the experiments. Problems in measuring this property [22] and failures in improving the theoretical description of particle nucleation phenomena [5,6] contribute to this. Future improvements in the model need to address these issues.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Difficulties to quantitatively describe the changes of the particle diameter in VA/BA emulsion copolymerization reactions were also reported by Saldívar et al [5], despite having used eight adjustable parameters to fit the experiments. Problems in measuring this property [22] and failures in improving the theoretical description of particle nucleation phenomena [5,6] contribute to this. Future improvements in the model need to address these issues.…”
Section: Resultsmentioning
confidence: 87%
“…In addition, a sensitivity analysis has shown that these parameters play an important role in the model predictions. A similar procedure has been adopted in the literature [4,5,22,23]. Tab.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instantaneous copolymer composition at various conversions was determined from the individual monomer to polymer conversions estimated by 1 H‐NMR, which, in general, showed that MA was consumed much more rapidly than VAc. The co‐monomer composition results were then fitted to the integrated version of the copolymerization composition (Mayo‐Lewis) equation 1, 40–42. Point estimates for reactivity ratio of MA ( r MA ) and reactivity ratio of VAc ( r VAc ) were determined to be 8.2 and 0.17, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hosseini et al [210] Sty 0-1 N Y Hosseini et al [23] Sty PB N Y Immanuel et al [211] VAc/BA PB N Y Immanuel et al [212] VAc/BA PB Y Y Jung and Gomes [26] Sty, BA 0-1/PB Y Y Kammona et al [213] Sty/2-EHA PB Y Y Kiparissides et al [214] VCM PB Y Y Marinangelo et al [215] Sty/BA PB N Y Meadows et al [216] Sty 0-1 N N Melis et al [217] VCM PB Y N Park et al [218] VAc/BA PB Y N Pohn et al [219] Sty 0-1 Y N Rajabi-Hamane and Engell [220] Sty PB N N Sajjadi [221] Sty 0-1-2-3 N Y Saldívar et al [4,[222][223][224] various binaries PB N Y Sood [225] Sty PB N N Sood [226] Sty PB N Y Sweetman et al [227] VAc/BA PB Y N Unzueta and Forcada [174] MMA/BA PB Y Y Vale and McKenna [38] VCM 0-1-2 Y Y Wulkow and Richards [228] -0-1-2 N Y Zeaiter et al [158,229] Sty…”
Section: Reference System Kinetics Coagulation Exp Validationmentioning
confidence: 99%